Transferência de funções ordinais através de classes de estímulos equivalentes: contribuições para a programação de ensino de adultos e crianças surdas e de crianças ouvintes - Sella, Ana Carolina (2009)
Currently, in Brazil, education for deaf people prioritizes the bilingual approach, in which the Brazilian Sign Language (LIBRAS) is taught as the first language, and the written Portuguese Language is taught as the instrumental language. The acquisition of the written Portuguese Language can be difficult for deaf people due to the differences between the ordinalgrammatical structures of the written Portuguese Language and the Brazilian Sign Language. The ordinal-grammatical structure of the first one consists in a subject verb object order, whereas the Brazilian Sign Language structure allows not only this order, but also different combinations of its elements. Such differences usually result, for the deaf people, in a writing repertoire of the Portuguese Language that has a different grammatical order than that one used by the verbal community in which they are inserted. The series of studies that are described here investigated variables that control the transfer of ordinal functions through equivalence classes. The general strategy was to establish three equivalence classes of four stimuli each (comprised of printed names, verbs and adverbs), then teach one name→verb→adverb sequence, comprised of one element from each class. In the first study, Study 1a, the initial repertoire of two deaf participants was tested through matching to sample (MTS) tasks comprised of pictures-printed words, signs printed words, printed wordspictures, signs-pictures, printed words-signs and pictures-signs relations. In Study 1b, the first four relations that were mentioned above were taught to the participants that responded with less that 90% of accuracy in Study 1a. In Study 1c, the same participants learned two new equivalence classes, adverbs and distracters that were comprised, respectively, of concrete nouns referring to places (e.g., farm/fazenda) and objects (e.g., cap/boné). In studies 2 a and 2b, in which two deaf adults took part, three equivalence classes were established with three members in each class, then one stimulus sequence, entailing one stimulus from each class, was taught. Finally, transfer of ordinal function was tested for five other sequences among eight possible new ones. In Studies 3a, 3b and 3c, with new participants, the number of stimulus in each class was increased to four before the stimulus sequence (A1→A2→A3) was taught. After teaching this sequence, transfer of function was tested for seven new sequences, among 12 possible new ones. All participants met the learning criterion in the matching to sample and sequence tasks. In the transfer of function tests there was a great variability in the results: some participants were exposed to one sequence teaching before showing transfer of ordinal functions; others were exposed to two sequences teaching. Other participants showed the emergence of sequencing behaviors without being exposed to sequence teaching. Questions that are discussed: 1) The use of instructions on the stimulus pairs in the matching to sample tasks; 2) the fact that some participants emitted sequencing responses before being taught to do so; 3) the fact that the participants emitted responses that showed generalization of the sequencing behavior towards new stimuli.